Cytotoxicity Effects of Polyhydroxybutyrate/Chitosan/Bioglass Nanocomposite Scaffolds on Human Osteoblast-like Cells (SAOS-2 Cells) - Batool Hashemi-Beni; Maryam Khoroushi; Saeed Karbasi; Fariba Heidari; Mohamad Reza Foroughi (Isfahan University of Medical Sciences, 2022)
In tissue engineering, a porous material is applied as the extracellular matrix or scaffold for cell growth. Then growth factors are added to this scaffold whose cytotoxicity must be assessed. In this study, the cytotoxicity effects of polyhydroxybutyrate/chitosan/bioglass nanocomposite scaffolds on human osteoblast-like cells (SAOS-2 cells) are explored.Materials&Methods:This study was experimental and was done in Isfahan Dental School. The polyhydroxybutyrate/chitosan/bioglass nanocomposite scaffold was fabricated using the electrospinning method. Scanning Electron Microscopy (SEM) analysis was used to evaluate the morphological characteristics of the nanofibers and their diameter distribution. Additionally, bioglass nanoparticles in the fibers were identified via SEM. The MTT assay was performed to assess cell viability after 3, 5, and 7 days.The collected data were analyzed using SPSS 20.0 through statistical tests including Kruskal-Wallis test (p value≤ 0.05).Results:According to SEM images, the scaffold fibers were fully porous and no beads were observed. Furthermore, the polyhydroxybutyrate/chitosan/bioglass scaffold showed greater cell viability and proliferation compared to the groups lacking bioglass.Conclusion:The polyhydroxybutyrate/chitosan/bioglass scaffold has no cytotoxic effect on osteoblast-like cells.